2022
DOI: 10.1186/s12884-022-05177-x
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ experiences with mHealth intervention for postnatal care utilisation in Nigeria: a qualitative study

Abstract: Background The postnatal period implies a crucial and delicate time for both the mother and the newborn. There is a growing body of evidence that is increasingly pointing to mHealth interventions as a potential tool for improved utilisation of maternal and child health services, including postnatal care. This can promote the health of mother and baby during this delicate period. However, the success of the interventions must be explored to validate their usefulness and reliability. Hence, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In LMICs, the first 2 years are generally reported to be the most high-risk period for U5M [ 49 ]. A study in Nigeria explored using a mobile health intervention (mHealth), which provides health promotion messaging on users’ mobile phones to promote the uptake and utilisation of postnatal care services [ 50 ]. The initiative is intended to increase women’s and partners’ knowledge about appropriate maternal-child care during the postpartum period [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In LMICs, the first 2 years are generally reported to be the most high-risk period for U5M [ 49 ]. A study in Nigeria explored using a mobile health intervention (mHealth), which provides health promotion messaging on users’ mobile phones to promote the uptake and utilisation of postnatal care services [ 50 ]. The initiative is intended to increase women’s and partners’ knowledge about appropriate maternal-child care during the postpartum period [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study in Nigeria explored using a mobile health intervention (mHealth), which provides health promotion messaging on users’ mobile phones to promote the uptake and utilisation of postnatal care services [ 50 ]. The initiative is intended to increase women’s and partners’ knowledge about appropriate maternal-child care during the postpartum period [ 50 ]. In this study, almost every participant reported feeling they had increased awareness of postnatal care and the importance of accessing these services for their newborns [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation